The molecular mechanism of propionate-regulating gluconeogenesis in bovine hepatocytes - Rui Pang; Xiao Xiao; Tiantian Mao; Jiajia Yu; Li Huang; Wei Xu; Yu Li; Wen Zhu (Animal Bioscience, 2023)
Objective Cows that are nursing get around 80% of their glucose from liver gluconeogenesis. Propionate, a significant precursor of liver gluconeogenesis, can regulate the key genes involved in hepatic gluconeogenesis expression, but its precise effects on the activity of enzymes have not yet been fully elucidated. Therefore, the aim of this study was to investigate the effects of propionate on the activity, gene expression, and protein abundance of the key enzymes involved in the gluconeogenesis of dairy cow hepatocytes. Methods The hepatocytes were cultured and treated with various concentrations of sodium propionate (0, 1.25, 2.50, 3.75, and 5.00 mM) for 12 h. Glucose content in the culture media was determined by an enzymatic coloring method. The activities of gluconeogenesis related enzymes were determined by enzyme linked immunosorbent assay kits, and the levels of gene expression and protein abundance of the enzymes were detected by real-time quantitative polymerase chain reaction and Western blot, respectively. Results Propionate supplementation considerably increased the amount of glucose in the culture medium compared to the control (p<0.05); while there was no discernible difference among the various treatment concentrations (p>0.05). The activities of cytoplasmic phosphoenolpyruvate carboxylase (PEPCK1), mitochondrial phosphoenolpyruvate carboxylase (PEPCK2), pyruvate carboxylase (PC), and glucose-6-phosphatase (G6PC) were increased with the addition of 2.50 and 3.75 mM propionate; the gene expressions and protein abundances of PEPCK1, PEPCK2, PC, and G6PC were increased by 3.75 mM propionate addition. Conclusion Propionate encouraged glucose synthesis in bovine hepatocytes, and 3.75 mM propionate directly increased the activities, gene expressions and protein abundances of PC, PEPCK1, PEPCK2, and G6PC in bovine hepatocytes, providing a theoretical basis of propionate-regulating gluconeogenesis in bovine hepatocytes.